Synthesis and superconducting properties of Tl₂-xBiSr₂Can-₁CunOy - Korbut, I.O.; Nedilko, S.A. (Functional Materials, 2015)
In the system Tl₂-xBiSr₂Can-₁CunOy (n = 2, 3, 0≤x≤0.5) the effect of initial composition on the ceramics phase composition was investigated. X-ray analysis and resistive measurements of the samples with different composition were carried out. The homogeneity region and change of the unit cell parameters were defined. Size and shape of the particles that
form the ceramics were studied using scanning electron microscopy. The electrophysical properties of the superconductors with addition of bismuth deteriorate, reducing the critical temperature in the superconducting transition.